Relationship between trace elements status and atrial fibrillation in patients with valvular heart diseases - Liu, Xiang; Shao, Yijia; Huang, Zirui; Huang, Jiayin; Han, Linjiang; Lu, Shaoyou; Guo, Haijiang; Liu, Jian (Frontiers in Cardiovascular Medicine, 2025)
BackgroundAtrial fibrillation (AF) combined with valvular heart disease (VHD) is increasingly prevalent worldwide and is associated with high morbidity and mortality. Studies have showed trace element concentrations varied in patients with AF and may be involved in the pathogenesis of AF. However, no data is currently available for those with VHD.MethodsUrine samples as well as clinical data were collected from 72 VHD patients with AF (VHDAF) and 72 VHD patients without AF (VHD) and further analyzed for a panel of trace elements: lithium, manganese, cobalt, copper, zinc, arsenic, selenium, strontium, Cadmium, mercury, thallium, lead. Quantile g-computation was adopted to explore the joint effect of the 12 trace elements on AF in this population, and internal validation was performed using 1,000 bootstrap re-samples.ResultsCompared with the VHD group, Sr levels were reduced, while Mn, Cu and Hg concentrations were increased in the VHDAF group. Quantile g-computation model indicated a significant association between the mixtures of the 12 urinary trace elements and AF in patients with heart valve disease (adjusted OR: 2.051; 95% CI: 1.180–3.565; p = 0.011). Positive partial effect was owing to Cu (weight: 0.43) and Hg (weight: 0.18), while negative partial effect mainly attributed to Sr (weight: 0.43) and Li (weight: 0.23).ConclusionVHDAF patients had higher Cu levels and lower Sr levels, and the two elements have been supposed to exert the largest influence on AF. Further research is needed to establish the causal relationships.